Differences between men and women regarding psychological meaning of sexual socialization practices among siblings - Enríquez Negrete, David Javier (2019)
Objective: to describe the psychological meaning of diverse of fraternal sexual socialization practices within a group of college students and determine whether there are significant differences among genders. Methods: cross-sectional study, non-probabilistic sample method (n = 214 college students) and the Modified Natural Semantic Networks were all used in order to analyze the psychological meaning of different practices of fraternal sexual socialization. Results: female participants were found to refer practices and meanings centered on an affective role, while men were centered on an instrumental role; however, there is a broad spectrum of socialization tactics shared by both men and women. Conclusion: gender and culture play a role in the fraternal sexual socialization practices that should be taken into account.